2019
DOI: 10.3390/rs11212570
|View full text |Cite
|
Sign up to set email alerts
|

Cold Bias of ERA5 Summertime Daily Maximum Land Surface Temperature over Iberian Peninsula

Abstract: Land surface temperature (LST) is a key variable in surface-atmosphere energy and water exchanges. The main goals of this study are to (i) evaluate the LST of the European Centre for Medium-Range Weather Forecasts (ECMWF) ERA-Interim and ERA5 reanalyses over Iberian Peninsula using the Satellite Application Facility on Land Surface Analysis (LSA-SAF) product and to (ii) understand the main drivers of the LST errors in the reanalysis. Simulations with the ECMWF land-surface model in offline mode (uncoupled) wer… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
84
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(92 citation statements)
references
References 35 publications
8
84
0
Order By: Relevance
“…Daytime and nighttime cases were analyzed separately, averaging half-hourly timeslots between 00:00UTC and 02:30UTC for nighttime and between 12:00UTC and 14:30UTC for daytime. In general, the results in Figure 4 are similar to those found in previous comparison studies between model skin temperature and satellite LST [10,11,88,89]. Namely, they show a tendency for model surface temperatures to have a lower daily amplitude, particularly over arid and semi-arid regions -see the strong negative daytime bias of −4 to −7 K over the Iberian Peninsula in July, of −2 K to −4 K over part/most of Northern Africa in July/January and of −1 K to −5 K in Southern Africa in January.…”
Section: In Situ Lstsupporting
confidence: 89%
See 3 more Smart Citations
“…Daytime and nighttime cases were analyzed separately, averaging half-hourly timeslots between 00:00UTC and 02:30UTC for nighttime and between 12:00UTC and 14:30UTC for daytime. In general, the results in Figure 4 are similar to those found in previous comparison studies between model skin temperature and satellite LST [10,11,88,89]. Namely, they show a tendency for model surface temperatures to have a lower daily amplitude, particularly over arid and semi-arid regions -see the strong negative daytime bias of −4 to −7 K over the Iberian Peninsula in July, of −2 K to −4 K over part/most of Northern Africa in July/January and of −1 K to −5 K in Southern Africa in January.…”
Section: In Situ Lstsupporting
confidence: 89%
“…In an attempt to increase the use of LST for climate-related studies, Good [8] explored relationships of LST and near-surface (2 m) air temperature over a number of standard weather stations worldwide. LST is also useful for assessing and improving parameters in surface schemes of numerical weather prediction (NWP) and Earth system models to provide more accurate surface and near-surface diagnostics [9][10][11]. It has been recognized that land surface models often struggle to correctly represent clear sky skin temperature (T skin ), particularly regarding its diurnal amplitude over arid and semi-arid regions with an underestimation of daytime and a small overestimation of night-time values [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The two reanalyses tended to overestimate LST at night and underestimate it in the summer daytime, which is consistent with previous results [40]. Johannsens [40] evaluated the impacts of vegetation parameters on ECMWF LSTs over the Iberian Penisula, by using GLCC (Global Land Cover Characterization which was also used in the reanalyses) and several other land-cover datasets. They found that the inaccuracies of vegetation cover used in the reanalyses could explain part of the discrepancy between the reanalyses and SEVIRI.…”
Section: Evo: Mediterranean Woody Savannasupporting
confidence: 85%